The Use of Arabic Quiet Book Media to Improve Students’ Writing Skills - Isna Adhani Purba; Akmal Walad Ahkas (Universitas Pahlawan Tuanku Tambusai, 2022)
This research is based on the existence of problems in learning Arabic writing skills in class VIII MTsS Al-Khairon. The problem is the lack of courage for class VIII students to express ideas, ideas and thoughts into Arabic writing correctly. This is due to the lack of media use in learning Arabic. This research is a classroom action research that aims to describe the improvement of student learning outcomes through Arabic quiet book media in learning Arabic in class VIII MTsS Al-Khairon. This research was conducted in two cycles with two meetings. The data collection method used is through learning outcomes tests. Furthermore, data analysis through individual test results and learning completeness results. The subjects in this study were class VIII MTsS Al-Khairon students in the even semester of 2021-2022, totaling 24 people (12 boys and 12 girls). The results showed that in the first cycle it was 53.33% and in the second cycle it increased to 84.37%. From the comparison of the cycle, there was an increase of 31.04%. So, it can be concluded that the use of quiet book Arabic media in learning Arabic can improve student learning outcomes.